2023
DOI: 10.1038/s41467-023-38446-0
|View full text |Cite
|
Sign up to set email alerts
|

Half-Heusler alloys as emerging high power density thermoelectric cooling materials

Abstract: To achieve optimal thermoelectric performance, it is crucial to manipulate the scattering processes within materials to decouple the transport of phonons and electrons. In half-Heusler (hH) compounds, selective defect reduction can significantly improve performance due to the weak electron-acoustic phonon interaction. This study utilized Sb-pressure controlled annealing process to modulate the microstructure and point defects of Nb0.55Ta0.40Ti0.05FeSb compound, resulting in a 100% increase in carrier mobility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In GeTe materials, heavy alloying, such as AgBiSe 2 -alloying, AgBiTe 2 -alloying, and Pb/Bi/Se-alloying, is used to realize the p–n transition, which induces the multidimensional defects and strengthens both carrier and phonon scattering. , The strong carrier-phonon scattering contributes to low μ / κ l (<410.7 cm 3 V –1 s –1 W –1 K) and ZT < 0.6. It should be noted that the carrier MFP (0.1–10 nm) and the phonon MFP (0.1–1000 nm) of GeTe do not overlap exactly, , which reveals the possibility of increasing μ / κ l by decoupling carrier-phonon scattering to realize high ZT .…”
Section: Introductionmentioning
confidence: 99%
“…In GeTe materials, heavy alloying, such as AgBiSe 2 -alloying, AgBiTe 2 -alloying, and Pb/Bi/Se-alloying, is used to realize the p–n transition, which induces the multidimensional defects and strengthens both carrier and phonon scattering. , The strong carrier-phonon scattering contributes to low μ / κ l (<410.7 cm 3 V –1 s –1 W –1 K) and ZT < 0.6. It should be noted that the carrier MFP (0.1–10 nm) and the phonon MFP (0.1–1000 nm) of GeTe do not overlap exactly, , which reveals the possibility of increasing μ / κ l by decoupling carrier-phonon scattering to realize high ZT .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Zhu et al have revealed that TE devices, made from HH alloys, are potential materials for TE cooling with high power density. 17 TE materials are used in aerospace for power generation or thermal management in space missions and unmanned aerial vehicles (UAVs) in the absence of traditional power sources. 18–20 HH alloy-based materials viz.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoelectric materials have become one of the hot issues in material science that can be applied to reduce waste heat [1]. Several theoretical approaches have been conducted to find suitable candidates for thermoelectric materials, such as Heusley alloy [2,3], metal dichalcogenides [4,5], and many others. Two different quantities can be investigated to predict the quality of thermoelectric materials, namely, the Seebeck and Nernst coefficients.…”
Section: Introductionmentioning
confidence: 99%